APPLICATION OF HOME AUTOMATION SYSTEM USING GOOGLE ASSISTANT - Ms. Preeti U. Melikatti; Mr. Vinayak V. Palmur (International Journal of Innovations in Engineering Research and Technology, 2022)
The research work presented here is an attempt to exaggerate on use of technology for the betterment of human beings. The research work has been done for using the Google assistant system for driving the home automation. The usefulness of this concept has been tested and analyzed further showing its advantages over other technologies available in the market today.